Long-term trends in income distribution: A global perspective - Thomas Obst (International Labour Organization (ILO), 2015)
This paper provides a comprehensive overview of the development in income distribution and outlines its major long-term trends of 23 countries worldwide. These countries are clustered in four groups covering the core advanced, the Nordic, the emerging, and the least developed economies of the world. This paper applies different measures to analyse income distribution in three dimensions: national income, functional income distribution, and personal income distribution. Depending on the indicators applied the time period ranges between 1960 and 2012. The empirical analysis shows that increases in national incomes are most pronounced in the advanced economies. The emerging economies also exhibit an upward trend in national income, but it has been less substantial. The least developed economies, however, have been detached from this trend and remain isolated. Moreover, this paper illustrates that there has been an enormous re-distribution of income. During the last three decades, the labour share of income has declined in nearly all countries under study. This development went hand in hand with increased personal income inequality. Disposable income inequality and market income inequality have both increased over the past 30 years. Wage dispersion also rose substantially contributing to greater income inequality. Additionally, the escalation of top income shares as well as the expansion of low paid employment has led to a growing gap between the top and the bottom income earners. This analysis also presents important interlinks between greater income inequality, the fall of the wage share, and increasing wage dispersion.
Keywords: 330; income distribution; wage differential; economic disparity; national income; household income; low income; trend; developed countries; developing countries